2013
DOI: 10.1590/s1983-14472013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida entre mulheres com excesso de peso e doenças crônicas não transmissíveis

Abstract: This study aimed to identify quality of life and its associated factors within women who are overweight and have noncommunicable diseases. It was a cross sectional study with a convenience sample of 50 adult and elderly women enrolled in an "Academia da Cidade" in Belo Horizonte, MG, Brazil. For quality of life assessment, the WHOQOL-bref was used. A descriptive analysis in addition to uni and multivariate linear regression were conducted. "Social relations" was the domain which most have contributed to qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
(15 reference statements)
1
5
0
5
Order By: Relevance
“…These fi ndings corroborate the results of our study, since affl icted the civil servants affl icted with a chronic health condition had better overall total scores, followed by those with two, and three chronic health conditions, who had a lower mean total score (12)(13) .…”
Section: Discussionsupporting
confidence: 90%
“…These fi ndings corroborate the results of our study, since affl icted the civil servants affl icted with a chronic health condition had better overall total scores, followed by those with two, and three chronic health conditions, who had a lower mean total score (12)(13) .…”
Section: Discussionsupporting
confidence: 90%
“…They highlighted that obese adolescents had worse QoL compared to the eutrophic group across all domains evaluated. Horta et al (2013) explored overweighed adult and elderly women with chronic non-communicable disease, using the WHOQOL-brief and showed that the “social relationship” domain is the one that contributed the most to QoL, followed by the “physical” domain. Our study replicated the results obtained by these two publications, extending the conclusions to another population (adult men and women).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies exploring the relationship between BMI and QoL in Brazil also had contradictory results. Adolescents ( Turco et al, 2013 ) and women ( Horta et al, 2013 ) with chronic non-communicable diseases experienced a similar impact of weight on QoL to samples in developing countries (QoL was negatively influenced by higher BMI). However, an interesting cross-cultural study involving Brazilian and Austrian women with Polycystic Ovary Syndrome demonstrated that for the Brazilian group, obesity was the factor having less impact on QoL, in contrast to the Austrian group, highlighting an influence of the cultural context on the obesity/QoL relationship (Hashimoto et al, 2003).…”
Section: Introductionmentioning
confidence: 87%
“…Observou-se ainda que a bebida mais consumida nas refeições é o suco de fruta industrializado (38%), seguido do refrigerante (29%) 11,12 . E quando se considera o consumo desenfreado de bebidas açucaradas, verifica-se um papel de destaque no desenvolvimento de doenças crônicas não transmissíveis (DCNT) -aquelas desenvolvidas no decorrer da vida e de longa duração (por exemplo: problemas cardiovasculares, câncer, diabetes e as doenças respiratórias crônicas) -sendo considerado um dos grandes problemas de saúde pública e atingindo cerca de 60% de mortes no mundo 13,14 . Existe clara associação entre o consumo de alimentos de baixo valor nutricional e os custos financeiros de hospitalizações e medicamentos para o controle dos problemas de saúde relacionados [15][16][17] .…”
Section: Introductionunclassified